Rubia cordifolia L. ameliorates DSS-induced ulcerative colitis in mice through dual inhibition of NLRP3 inflammasome and IL-6/JAK2/STAT3 pathways. Issue 8 (August 2022) - Qin, Wei; Luo, Han; Yang, Liu; Hu, Di; Jiang, Su-Ping; Peng, Dai-Yin; Hu, Jiang-Miao; Liu, Shou-Jin
Abstract: The aerial part of ​ Rubia cordifolia  ​L. has been used as an herbal medicine for a long time with various pharmacological activities, including anti-inflammatory, anticancer, and antibacterial activities. The most notable usage of these was that this herbal medicine had good therapeutic effects on diarrhea caused by various factors. However, the mechanism for the ethanolic extract of ​ R. cordifolia  ​L. (RCEE) to treat Ulcerative colitis (UC) effectively is still unclear. In this study, DSS successfully induced UC mice and then intervene using different polar parts of RCEE. The results indicated that RCEE-treatment inhibited colonic combination NLRP3 inflammasome formation and IL-6/JAK2/STAT3 activation in vivo, significantly ameliorating the clinical symptoms, including alleviating colonic mucosal damage and infiltration of macrophages, suppressing the release of inflammatory cytokines, and reducing mortality. Taken together, this study suggests that dual inhibition of NLRP3 inflammasome and IL-6/JAK2/STAT3 pathways activation using RCEE may be a promising therapeutic strategy for preventing the progression of UC. Abstract : Rubia cordifolia L., Ulcerative colitis, NLRP3 inflammasome, IL-6/JAK2/STAT3 pathways.